El sistema penitenciario ecuatoriano. Sin luz al final del túnel (Tema Central) - González Malla, Janeth Patricia (2024)
Why is the prison crisis in Ecuador not solved? is the question that leads us to explore the penitentiary problem from its origins to the current Ecuadorian context. The objective is to reflect and demonstrate that prisons and deprivation of liberty have maintained the same dynamic since their origins, causing suffering and pain to inmates, in contrast to the resocializing purpose of punishment; The current context shows that prison management has not evolved, despite the scientific and regulatory development of this branch. The qualitative and socio-legal approach is the basis of the research because through the narrative design the history of the penitentiary system, the regulatory advance, and are compared with social reality are sequentially described; That is, an approach to the right to society is made through the documentary review of secondary sources. In short, it is concluded that there is no political will of the State to address the problem technically and with specialized personnel as suggested by the doctrine; on the contrary, the prison crisis in Ecuador has an anachronistic, dehumanizing tone and is far from the purpose of the sorrow; That is, there is no rehabilitation or resocialization.